Retrointegration2023—Papers from the 7th International Conference on Retroviral Integration - Alan N. Engelman; Duane P. Grandgenett; Goedele N. Maertens; Kristine E. Yoder; Mamuka Kvaratskhelia (Viruses)
The integration of retroviral DNA into host chromosomal DNA is a landmark event that demarcates the transition from the early steps of virus replication to post-integration gene expression and the assembly of new virus particles [...]